JURIDICAL REVIEW OF THE IMPLEMENTATION OF EARLY MARRIAGE (MERARIQ KODEQ) IN SASAK CUSTOMS IN REVIEW OF THE MARRIAGE LAW (STUDY IN LEPAK VILLAGE, SAKRA TIMUR SUB-DISTRICT, EAST LOMBOK DISTRICT) - Pahmi Adrian; Anies Prima Dewi; Imawanto Imawanto (Media Keadilan: Jurnal Ilmu Hukum, 2024)
The purpose of this study is to determine the form of early marriage arrangements (merarik kodeq) based on the Marriage Law and to identify the factors that lead to the implementation of early marriage (merarik kodeq) in Sasak customs in Lepak Village, Sakra East District, East Lombok Regency. This study will serve as a basis for further research on this topic. The study employed a normative empirical research method, which entailed a review of laws and regulations and interviews with community members, village officials, religious leaders, traditional leaders, hamlet heads, and their staff. The results of the study are presented in the form of an implementation model for early marriage (merariq kodeq), which is a custom or habit of the community, especially the Sasak tribe. This practice is not common and cannot be denied, therefore the village government is unable to take any action. To prohibit it completely would be to ignore the Sasak language term "Betungkem rarely," which means that if there is a case such as early marriage, it can only be accepted with a yes, whether it is going forward or backward. In essence, this is just a mediator in this matter.